Development of Curcuma Caesia (Black Turmeric) Cultivation as a Leading Local Traditional Medicine Plant - Koko Bustami; Muhammad Saifrizal; Mizan Maulana; M. Ferdiananda Chadafi; Abdullah Abdullah (LPPM UIKA Bogor, 2022)
Development of Curcuma Caesia (Black Turmeric) Cultivation as a Local Superior Traditional Medicinal Plant which was carried out in Kekuyang Village, Ketol District, Central Aceh Regency. Our motivation for carrying out this activity, based on the search results, found a lack of understanding of community literacy regarding traditional medicinal plants that can be used as income, namely black turmeric, the minimum amount of fertilizer available, the number of farmers, the number of pesticides and the number of seeds also affect the productivity of black turmeric, in addition to land use which can be used as a location for the biodiversity of medicinal plants has not yet been found. It is hoped that the purpose of this service can provide community understanding regarding the mapping of the biodiversity of local superior traditional medicinal plants, provide public understanding of the benefits and efficacy of black turmeric as a traditional medicinal plant, then form conservation groups, carry out conservation by cultivating rare medicinal plants throughout the region so that the area has a branding as a center for the conservation of medicinal plant biodiversity and makes the conservation center a center for medicinal plant education with a conservation group as the main tutor as well as a center for the medicinal plant business. The implementation method is by way of roadmap mapping, carrying out the stages of activities starting from identifying needs, briefly describing the target audience, planning forms of intervention, establishing partnerships with parties outside the village, mapping success, and measuring and implementing the program. The results of the activity show that the great potential that Kekuyang Village has to expand black turmeric production is supported by the condition of the fertile area, the participation of farmers, and also the support of residents and village apparatus in this program which is very responsive and supported by Reje (village head) to advance the area by introducing all over the world and also accepting all forms of investment in potential agriculture.